ANALISIS TUTURAN BAHASA ASING DALAM FORUM PRESENTASI MAHASISWA - hanipah arif (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The research used is related to foreign languages, namely languages that are used in a particular area. The use of foreign languages is often used by various groups of people, both in the area or outside the language area itself. On this occasion the researcher will analyze about foreign languages in the student presentation forum, because the presentation activity is a forum for conveying various opinions of learning activities. Then the presentation forum can also be said to be the center of language variation. The purpose of this research is to find out and analyze the speech acts of students involving foreign languages in learning activities. The use of foreign languages in this presentation forum researchers used descriptive qualitative methods for data processing. Researchers take data using video, listen and look for foreign languages contained in the video based on the type of meaning in a foreign language. The results of the study stated that from the various videos that researchers found there were only 18 words from foreign languages mentioned by students in the videos that were obtained.